1997
DOI: 10.1021/js960453v
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Pharmacokinetics of Bisoprolol After Intravenous and Oral Administration in Beagle Dogs

Abstract: The stereoselective pharmacokinetics of bisoprolol, a highly beta 1-selective adrenoceptor blocking agent, was studied in dogs. After intravenous and oral administration of the racemate, there was a difference in the plasma concentration between S(-)- and R(+)-bisoprolol. The area under the curve (AUC) of concentration versus time of S(-)-bisoprolol was approximately 1.5 times higher than that of R(+)-bisoprolol and the elimination half-life of S(-)-bisoprolol was approximately 1.4 times longer than that of R(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Differences in values have been reported in man for the unbound enantiomers of pindolol (Hsyu & Giacomini 1985;Somogyi et al 1992), disopyramide (Lima et al 1985) and amphetamine (Hutchaleelaha et al 1994); all underwent secretion in addition to filtration and, presumably, the observations reflected differences in secretory transport between isomers. However, there were no differences in the renal clearance of the unbound enantiomers of methadone (Foster et al 2000) and bisoprolol (Horikiri et al 1997), nor in inhibition by the enantiomers of pindolol, disopyramide and bupivacaine on the transport of tetraethylammonium across vesicles prepared from the apical membrane (referred to as brush-border membrane vesicles by the authors) (Gross & Somogyi 1994). Furthermore, inhibition by pindolol of the uptake of N-methylnicotinamide by these vesicles was not stereoselective (Ott et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in values have been reported in man for the unbound enantiomers of pindolol (Hsyu & Giacomini 1985;Somogyi et al 1992), disopyramide (Lima et al 1985) and amphetamine (Hutchaleelaha et al 1994); all underwent secretion in addition to filtration and, presumably, the observations reflected differences in secretory transport between isomers. However, there were no differences in the renal clearance of the unbound enantiomers of methadone (Foster et al 2000) and bisoprolol (Horikiri et al 1997), nor in inhibition by the enantiomers of pindolol, disopyramide and bupivacaine on the transport of tetraethylammonium across vesicles prepared from the apical membrane (referred to as brush-border membrane vesicles by the authors) (Gross & Somogyi 1994). Furthermore, inhibition by pindolol of the uptake of N-methylnicotinamide by these vesicles was not stereoselective (Ott et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, 10 the distinctive stereoselectivity in the pharmacokinetics of bisoprolol in dogs was found when racemic bisoprolol was intravenously and orally administered. The plasma AUC and half-life of (S)-(-)bisoprolol were significantly greater than those of (R)-(+)bisoprolol.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, it was concluded that the stereoselective disposition of enantiomers in dogs was brought about by a difference in the metabolic clearance between (S)-(-)-and (R)-(+)-bisoprolol. 10 The aim of the present study was to characterize the difference in plasma and urinary pharmacokinetics of bisoprolol enantiomers in human subjects. In addition, an in vitro study was performed to assess the role of human cytochrome P450 (CYP) isoforms in mediating the major pathways of bisoprolol metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…To appropriately define the process mechanistically, blood measurements and clearance by that pathway should be determined. A good example of this is provided by bisoprolol [73]. The urinary recovery ratio of S:R enantiomer was 1.29 in urine, whereas renal clearance was essentially nonstereoselective (S:R ratio ¼ 0:96).…”
Section: Excretionmentioning
confidence: 99%